(untitled) (The Review of Diabetic Studies, 2024)
In the past, Saudi Arabia’s nursing education system was heavily influenced by traditional methods, and there were very few formal training courses. However, the Kingdom recognized the importance of nurses in healthcare delivery and embarked on a comprehensive reform effort to enhance nursing education. This shift has led to the emergence of specialized nursing schools as well as the need for innovative teaching methods and new curricula. In recent decades, Saudi Arabia has partnered more with foreign institutions and organizations in an effort to adopt nursing education practices from other countries. This present study evaluates the scenario in terms of secondary data and presented the same as review study. The time line of the data was from 2010 to 2022.